Retrodictive mentalising abilities of individuals with and without autism spectrum disorder - Pillai, Dhanya R. (2014)
The aim of this thesis was to investigate the retrodictive mentalising abilities (a kind of backwards inference from a mental state to its causal antecedent in order to make sense of others’ behaviours) of people with and without Autism Spectrum Disorder (ASD). A new experimental paradigm was developed in order to examine people’s ability to make sense of others’ behaviours in a way that closely resembles the intricacies of real-world settings. The stimuli utilised in this thesis portrayed people’s spontaneous and genuine responses during four specific events (scenarios). People were told a joke in the Joke scenario whereas in the Story scenario the researcher related a series of unfortunate mishaps that she experienced earlier in the day. In the Compliments scenario, people were told a series of compliments while in the Waiting scenario the researcher performed irrelevant tasks during an experiment whilst the person was kept waiting. Participants viewed brief videoclips of these behavioural responses and were asked to determine which event had previously occurred to the people in the videoclips. Participants eye movements were recorded to ascertain the visual strategies used. Typically developing individuals successfully inferred the events that occurred by viewing brief samples of behavioural reactions of typically developing individuals (Experiment 1). It was found that scenario experienced did not impact how targets self-reported their level of empathic ability (Experiment 2). While people with ASD were able to infer people’s behavioural responses, their performance on the task was inferior as compared to typically developing individuals (Experiment 3). Participants varied their gaze strategies depending on the event experienced by the people in the videoclips and they had a tendency to focus more on the mouth compared to the eye region of the face (Experiment 1 and 3). When participants viewed videoclips of behavioural responses of people with and without ASD to the same events, they were more successful at inferring the reactions to the events which occurred when viewing videoclips of neurotypical individuals as opposed to individuals with ASD (Experiment 4). Furthermore, participants were unable to identify the reactions to two of the four events when viewing videoclips of people with ASD.